Perancangan Zona Layanan dan Rute Bus Sekolah Kota Payakumbuh Menggunakan Graph Neural Network (GNN) - Rizky Ferdiansyah Habibi NST; Arie Yulfa (Geosfera: Jurnal Penelitian Geografi, 2025)
Payakumbuh City is one of the cities located in West Sumatra Province, with a population of 149,077 people. Public transportation is needed for daily mobility, especially for students, because public transportation in this city only consists of 21 units and only serves one route. This study aims to establish service zones, routes, stops or bus stops, and bus transportation modes that are suitable for the geographical conditions of Payakumbuh City. The method used in this study is Graph Neural Network (GNN) with the variables analyzed being the distribution of schools, traffic congestion points, points of interest, and road networks. The results of the study show that service zones can be determined based on the existing land use in Payakumbuh City, dividing the service zones into 4 zones with a total route length of 93.54 kilometers, 209 bus stops, and a suitable mode of transportation, namely microbuses with two types of buses, with an estimated number of 211 units. Payakumbuh City can implement public transportation, particularly school buses, but special attention must be given to the existing road conditions, as the road width in the area is 4-7 meters. Therefore, in its implementation, three service zones can use microbuses with a capacity of 30 passengers, and one service zone can use microbuses with a capacity of 20 passengers.